Use of inorganic fertilizers in Uganda - Namazzi, Juliet (International Food Policy Research Institute, 2008)
Improving agricultural productivity is vital for poor rural households in Uganda to meet their food security needs and to promote sustained increases in income. Inorganic fertilizer can be a powerful productivity enhancing input. While Uganda has one of the highest soil nutrient depletion rates in the world, it has one of the lowest rates of annual inorganic fertilizer application – only 1.8 kg per hectare. The World Bank calculated that the value of replacing these depleted soil nutrients could be 20 percent of average rural Ugandan household income. Promoting fertilizer use is therefore crucial to sustainably increase agricultural productivity in Uganda. This brief explores the economics of fertilizer use by smallholder farmers in Uganda, the determinants of fertilizer use, and options for government action.